Mechanical Behaviour of High-Strength Aluminium Alloys Influenced by Dynamic Strain Ageing - Hörnqvist, Magnus (My University, 2003)
The effect of dynamic strain ageing during monotonic tensile and shear deformation has been rather extensively characterized during the last five decades. However, relatively little is known about the influence of DSA on the fatigue properties. This is to be investigated for high strength aluminium alloys, such as the 7000 series used extensively in the aerospace industry, during a PhD project at the Department of Materials Science and Engineering at Chalmers. As the start of this project an extensive literature review is made to collect the scattered information available. As a background both dynamic strain ageing under simple tensile deformation as well as fatigue properties of high-strength aluminium alloys are reviewed, covering both theory and practice. Furthermore, characterization of such a high-strength Al-alloy, namely 7030, is made by use of tensile tests. This is done to establish the mechanical behaviour in the temperature and strain rate range proposed for further fatigue investigation. Along with this, some background tests regarding room and low temperature ageing behaviour of the solution treated material are performed. The tests show that 7030 would serve as a suitable material for further investigations into the relationship between dynamic strain ageing and fatigue. Both in the solution treated and peak-aged condition serrated flow was recorded under a variety of deformation conditions, along with surface markings known to originate from the Portevin-Le Chatelier effect. The solution treated samples also showed the characteristic inverse temperature dependence of the flow stress and negative strain rate sensitivity, which were both absent in the peak-aged condition. Another interesting feature was the type D serrations present in all solution treated samples. This has not been reported earlier for this material under similar deformation conditions. Due to the limited amount of tests performed in this study, most of the results obtained regarding critical strains are considered as preliminary and require further investigation. The ageing tests showed that samples in the solution treated state are not stable for the duration of a fatigue test, which is often in the order of hours. A more stable state is obtained if the material is naturally aged for approximately 24 h. The material is then of course not strictly solution treated but at least the material properties will remain constant during the tests. The type D serrations observed were proposed to be related to this state of the material. The problem of unstable microstructure still remains for tests performed above room temperature, but no practical way has been found to deal with is. Furthermore, the natural ageing is delayed to considerably longer times if the quenched material is stored at low temperatures (-20ºC), something that can be used when storing heat treated specimens.
Keywords: Materialteknik; Materials Engineering